Growth charts for individuals with rhizomelic chondrodysplasia punctata. Issue 1 (12th September 2016) - Duker, Angela L.; Niiler, Tim; Eldridge, Grant; Brereton, Nga H.; Braverman, Nancy E.; Bober, Michael B.
Abstract : Rhizomelic chondrodysplasia punctata (RCDP) is a class of peroxisomal disorders characterized by defective plasmalogen biosynthesis. There are multiple recognized types of RCDP, all of which have autosomal recessive inheritance, and their associated genes are known: RCDP type 1 with PEX7, RCDP type 2 with GNPAT, RCDP type 3 with AGPS, RCDP type 4 with FAR1, and RCDP type 5 with PEX5 . Among other medical/developmental issues, plasmalogen deficiency has a direct effect on bone growth and results in postnatal growth failure, the severity of which corresponds to the degree of plasmalogen deficiency. In order to document growth in patients with RCDP, we present detailed growth curves for length, weight, and head circumference derived from retrospective data from 23 individuals with RCDP types 1 and 2 confirmed by molecular and/or biochemical studies. We stratified growth curves by age as well as by plasmalogen level, with those with higher plasmalogens grouped as "non‐classic." The growth charts presented here provide guidance to families and physician caretakers on the natural course of growth in individuals with RCDP during infancy into early childhood, and thus will have particular utility in setting expectations and guiding optimal feeding interventions in this population.© 2016 Wiley Periodicals, Inc.